Edoardo Tresoldi and the heteronomy of architecture - Tresoldi, Edoardo (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The Heteronomy of architecture «is understood as the condition to be pursued if one sets one’s goal of producing buildings that belong to one’s own time, to the complex interweaving of values and needs that characterise it, to the place where they arise»1. Heteronomy in architecture allows us to break the boundaries still linked to the concept of the now obsolete scientific sector. The breaking of these boundaries makes a trans-disciplinary contribution possible and consequently leads us to having a transversal vision. One of the people who recently successfully pursued the road of the Heteronomy of architecture and art through a borderline path is Edoardo Tresoldi, an Italian sculptor who «investigates the poetics of the dialogue between man and landscape using architectural language as an expressive tool and key to reading space». The artist plays with the transparency of the metal mesh to transcend the space-time dimension and narrate a dialogue between Art and World, a visual synthesis that reveals itself in the fading of the physical limits of his works2.